POTENSI DAN DAYA DUKUNG LESTARI TEGAKAN AREN DI DESA LANNE - Dewi Indasary; Nurul Hikmah Melilani; Muhammad Ramdhan Rachmat; Suhasman Suhasman (Forestry Faculty of Universitas Hasanuddin, 2019)
Palm trees have high economic potential because almost all parties can provide financial benefits. But of all palm products, the palm sap that comes from the male flower arm as an ingredient for the production of brown sugar is the greatest economic value. However, there are some people who prefer to cut palm trees for cultural purposes instead of properly handling them to be used as brown sugar. This research aims to analyze the carrying capacity and potential of palm trees in Lanne Village. The location of this investigation was carried out in Lanne Village, Tondong Tallasa District, Pangkajene and Kepulauan Regency, South Sulawesi Province. The location of the sugar palm administrators is in two villages, namely, Manjalling and Mariololo. The research method used is a qualitative research method that uses inventory, observation and interview techniques. The results obtained are that for now the people of Lanne do not comply with the capacity of sustainable cargo. The presence of sugar palm is now relatively minor. Therefore, to restore the glory of the sugar palm sugar population must be added